Perianal lesions after return from Togo: An isolated cutaneous manifestation of schistosomiasis. Issue 6 (1st November 2016) - Note, Stéphanie; Vanbrabant, Peter; Soentjens, Patrick
Abstract : Isolated perianal lesions in a returned traveller from Togo were observed. Eosinophilia was the lead to schistosomiasis, although no systemic symptoms were reported. This case report of cutaneous schistosomiasis demonstrates the importance of a travel history, especially geographic and exposure features, and treats the differential diagnosis of eosinophilia in a returned traveller with skin lesions.